Cationic terminal borylene complexes: structure/bonding analysis and [4+1] cycloaddition reactivity of a BN vinylidene analogue. - Aldridge, S; Jones, C; Gans-Eichler, T; Stasch, A; Kays, D; Coombs, N; Willock, D (2006)
(Chemical Equation Presented) Charge changes everything: The cationic terminal aminoborylene complex [CpFe(CO)2(BNCy2)] +[BArF4]- (1, Cy = cyclohexyl, ArF = 3,5-(CF3)2C6H3; Fe orange, B green, N blue, O red, C gray) was structurally characterized. DFT studies (see HOMO-2) indicate delocalized π bonding along the linear Fe-B-N framework and significant Fe-B and B-N multiple-bond character. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.